Rice - cassava + pulse system for productivity, profitability and energy efficiency - G. Suja,; J. Sreekumar,; S. Sunitha,; Jacob John, (Annals of Agricultural Research, 2025)
Cropping systems involving short-duration cassava ensures food, nutrition and livelihood security besides resilience under climate change. A field experiment was conducted for two years to evaluate the scope of inclusion of short-duration cassava with pulse crops in rice-based system at ICAR-Central Tuber Crops Research Institute, Thiruvananthapuram, Kerala. Rice var. Kanchana was sown in first season followed by short-duration cassava (var. Sree Vijaya and Vellayani Hraswa) intercropped with pulse crops, green gram (var. Co-Gg-7), black gram (var. Co-6) and soybean (var. JS-95-60) under two fertility levels (full FYM, full N, no P and full K (FYM @ 12.5 t ha-1, NPK @ 100:0:100 kg ha-1); half FYM, half N and full K (FYM @ 6.25 t ha-1, NPK @ 50:0:100 kg ha-1). Intercropping short-duration cassava (either of the varieties) with black gram under reduced fertilizer level proved feasible. The nutrient uptake of cassava in this treatment was on par with sole cassava. There was improvement in soil fertility by enhancing organic C, available N and P status of soil, which enabled saving of nutrients. Rice var. Kanchana followed by short-duration cassava var. Sree Vijaya + black gram var. Co-6 was productive (tuber yield, 26.67 t ha-1; tuber equivalent yield, 40.19 t ha-1; production efficiency, 111.64 kg ha-1day-1), energy a (191.11 x 103 MJ ha-1) and profitable (added profit of `61736 per ha over sole cassava), besides saving half FYM and N and all P.